The Prosody of Rhetorical and Information-Seeking Questions in German. (December 2019) - Braun, Bettina; Dehé, Nicole; Neitsch, Jana; Wochner, Daniela; Zahner, Katharina
This paper reports on the prosody of rhetorical questions (RQs) and information-seeking questions (ISQs) in German for two question types—polar questions and constituent questions (henceforth " wh -questions"). The results are as follows: Phonologically, polar RQs were mainly realized with H-% (high plateau), while polar ISQs mostly ended in H-^H% (high-rise). Wh -RQs almost exclusively terminated in a low edge tone, whereas wh -ISQs allowed for more tonal variation (L-%, L-H%, H-^H%). Irrespective of question type, RQs were mainly produced with L*+H accents. Phonetically, RQs were more often realized with breathy voice quality than ISQs, in particular in the beginning of the interrogative. Furthermore, they were produced with longer constituent durations than ISQs, in particular at the end of the interrogative. While the difference between RQs and ISQs is reflected in the intonational terminus of the utterance, this does not happen in the way suggested in the semantic literature, and in addition, accent type and phonetic parameters also play a role. Crucially, a simple distinction between rising and falling intonation is insufficient to capture the realization of the different illocution types (RQs, ISQs), against frequent claims in the semantic and pragmatic literature. We suggest alternative ways to interpret the findings.